Recovery process of jacalin from crude protein of jackfruit seed powder : optimization of extraction and cytotoxicity study of jacalin towards human cancer cell - Zuraidah, Ali (2015)
Jacalin is a major lectin present in jackfruit seeds, obtained by crude protein recovery. Its lectin symbol is AIL and it belongs to the galactose family of N-acetylgalactosamine binding lectins, which are recognized to be cancer cell inhibitor. There have been many pharmacological research studies focusing intensively on jacalin, however their scope was restricted to the application of jacalin in pharmacology. Although there are methods for producing jacalin, they are still limited owing to its low productivity. Low yield production compared to high demands in the pharmacy industry increases the price of jacalin. An understanding of the recovery and extraction process as well as separation process behavior can be obtained via research and experimentation in order to determine the optimum extraction and separation conditions of jacalin production. The optimum conditions of crude protein recovery are very important as they contribute to attaining high yield extraction of jacalin as well. However, the optimum soaking pretreatment time was determined prior recovery process conducted. The parameters that mainly influence crude protein recovery are liquid to solid ratio (LSR), temperature and recovery time. The independent variables were investigated using One-Factorial-At-Time (OFAT) approach prior to optimizing the recovery process by response surface methodology (RSM). The recovery of crude protein with optimum conditions was followed by extraction of jacalin from crude protein. Liquid-liquid extraction by reversed micelles method was used in the extraction of jacalin from crude protein, by studying two variables; salt concentration (NaCl) and pH value. Crude protein and jacalin extract were applied to two cancer cell lines, human breast cancer cell (MCF7) and non-small lung carcinoma cell (H1299), in comparison to jacalin standard. In studying the soaking pretreatment time effect, it was determined that 6 hr was the optimum soaking time. Meanwhile, the OFAT study showed that three variables, LSR, temperature and recovery time were influence in crude protein recovery and the optimization was achieved using RSM, which 29.11 % increased with 42.84 mg/mL. The reversed micelles system was successfully used to extracting jacalin from the crude protein of jackfruit seed powder, with optimum pH of 6.0 and salt concentration up to 0.2 M resulting in jacalin concentrations of 1.782 mg/mL. The jacalin extract was more effective compared to crude protein in inhibiting the viability for both of cancer cell. IC50 for MCF7 was achieved at concentration 125 μg/mL, closely comparable to jacalin standard with only 1.60 % contradictions. Thus, reversed micelles extraction method can be proposed to use as a purification method for jacalin, besides, this method is easy to scale up and operate continuously. Furthermore, recommended that further research on others parameter effect of crude protein recovery such as particle size of jackfruit seed powder and using variety species of jackfruit seed 1